Speech intelligibility test methodology applied to powered air-purifying respirators used in healthcare. Issue 1 (13th November 2020) - Xu, Susan; Simons, Jeremy; Yorio, Patrick; Rottach, Dana; Zhuang, Ziqing; Radonovich, Lewis
Abstract: Powered air-purifying respirators (PAPRs) are worn to protect workers from hazardous respiratory exposures in a wide range of workplaces, including healthcare. However, PAPRs may diminish the ability of wearers to correctly hear words spoken by others, potentially interfering with safe performance of healthcare duties. Accordingly, the impact of PAPRs during healthcare use on speech intelligibility (SI) and consequently on user safety, usability, and patient care is not well studied. The objectives of this study were to (1) determine a listener's ability to comprehend single-syllable words spoken by a PAPR wearer; (2) determine a PAPR wearer's ability to intelligibly hear and identify single-syllable words spoken by a PAPR wearer; (3) to assess the variability between speakers, listeners, and PAPR models; (4) to investigate the effects of PAPR design features on SI; and (5) inform a SI requirement for certifying future PAPRs for use in healthcare. This study utilized a Modified Rhyme Test to assess SI for PAPRs. The current National Institute for Occupational Safety and Health (NIOSH) methods for assessing SI are limited to the recently introduced PAPR100 respirator class and the class of respirators claiming chemical, biological, radiological, and nuclear (CBRN) protections. Four NIOSH-approved PAPRs were evaluated using four human subjects. Four experimental conditions were examined:(1) Speaker and Listener with no PAPR; (2) Speaker and Listener both wearing PAPRs; (3) Speaker with a PAPR, Listener without a PAPR; and (4) Speaker without a PAPR, Listener with a PAPR resulted in a total of 144 experiments. Statistical analysis showed that the SI performance ratings were not significantly different among the PAPR models, but experimental conditions had significant impact on SI. The pattern of SI across the conditions of the experiment also showed a significant difference depending on PAPR model. The SI performance rating for all PAPRs could meet the current NIOSH CBRN certification requirement for speech intelligibility.